Stigma, mental illness, and COVID-19 from a frontline clinician perspective: a way to go against the grain? - Branca, Francesco; Macchiarulo, Elena; Costanza, Alessandra; Ambrosetti, Julia; Amerio, Andrea; Aguglia, Andrea; Serafini, Gianluca; Amore, Mario; Merli, Roberto (Acta Biomedica Atenei Parmensis, 2021)
A well-known insidious obstacle for patients with mental illness is stigma, linked to feelings of incomprehensibility, incurability, and dangerousness. The COVID-19 pandemic represented a relevant additional barrier for these patients, which contributed to their marginalization, quality of life reduction and diminished treatments feasibility. As part of a cross-sectional multidisciplinary project conducted in the psychiatric service of Biella, a northern Italy province, preliminary data were collected by frontline clinicians during the COVID-19 first wave regarding the vicious cycle that may have been created between stigma and psychiatric patients in COVID-19 time. Therefore, we tried to frame the observed changes not in the dual literature paradigms stigma-mental illness or stigma-social consequences in COVID-19 time, but in the mental illness-stigma-COVID-19 three-way paradigm. The protection of this vulnerable segment of population, including a rapid access to COVID-19 vaccination, needs to be recognized as a real public health priority. The role of mental health services in providing information and activating supportive interventions for patients with mental illness is also crucial. Particularly, a multidisciplinary therapeutic team including mental health providers, general practitioners, hospital physicians, and social services would be needed to ensure adequate networks and cares continuity. Actions to contrast stigma can be arduous and exhausting because they must counteract the gravitational pull of customs, prejudices, and ingrained cultural beliefs, and may therefore appear to be moving in an "unnatural" direction, like the water in Escher’s lithograph entitled "Waterfall". Nevertheless, there is no less strenuous way to go against the grain.